PERILAKU KECANDUAN MEROKOK DAN HUBUNGAN SOSIAL DENGAN LAWAN JENIS SISWA SMKN 3 PEKANBARU - Admida, Tri; Rosmawati, Rosmawati; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Male students who are addicted to smoking tend to be more comfortable with their male friends and rarely seen together with their female friends. The purpose of this study is 1) To identify smoking addiction behavior of SMK Negeri 3 Pekanbaru students. 2) To identify the overview of social relations with the opposite sex students who are addicted to smoking in SMK Negeri 3 Pekanbaru. The design of this study is based on quantitative descriptive research. The subjects of this studywere all students included in the indicators of smoking addiction behavior. Smoking addiction behavior and social relations with the opposite questionnaire were used in this study. The results of this study showed that the behavior of the students who are addicted to smoking included in the medium category with students’ social relations with opposite sex who were included in the high category about six students and students who had smoking addiction behavior and social relations in the medium category about six students. The result proved that eventhough students have a smoking addiction behavior, they still have good social relations with their opposite sex. In other words, there is no influence between smoking addiction and the destruction of social relations between the opposite sex.Key Word : Behavior, Smoking Addiction, Social Relations With The Opposite Sex.